Análise das caracterísicas anatômias relacionadas à fístula perianal utilizando ultrassom anorretal tridimensional - Buchen, Guilherme Moreira (2014)
Background:Surgery for anal fistula is often associated with continence disorders due to the transection of sphincter muscles. Extensive knowledge of anal canal anatomy and anal fistula can help prevent this outcome. Objective:Correlate the anatomical conformation of the anal canal, fistula track and the internal opening according to gender and hemicircumference (anterior vs. posterior) using 3-D ultrasonography. Methods:165 patients with fistula were evaluated with 3-D ultrasound and grouped according to gender, fistula type, internal opening and track position. Fistulae were transsphincteric in 128 and intersphincteric in 37 subjects. The study measured the external and internal anal sphincter, the puborectalis, the distance from the internal opening to the distal edge of the external and internal sphincter, the length of the internal and external sphincter compromised by the track and the percentage of compromised muscle. Results:Muscles were longer in males. The distance from the internal opening to the internal sphincter was greater for the posterior hemicircumference. The point where the fistulous track crossed the anterior external sphincter was similar for the two genders but the compromised muscle percentage was greater in females. The point where the fistulous track crossed the internal sphincter was similar for the two genders but the percentage of compromised internal sphincter was greater in males for the posterior hemicircumference. The study was limited by the absence of testing for interobserver and intraobserver agreement. Conclusion:The anal canal muscles are longer in males and the pectinate line is asymmetrical. In females, the percentage of compromised external sphincter was greater in the anterior hemicircumference due to the shorter external sphincter, while in males the percentage of compromised internal sphincter was greater in the posterior hemicircumference Keywords: Anal Fistula. Anorectal Three-dimensional Ultrasound.